2009
DOI: 10.1097/ede.0b013e3181a71279
|View full text |Cite
|
Sign up to set email alerts
|

Hormone Replacement Therapy, Family History, and Breast Cancer Risk Among Postmenopausal Women

Abstract: Background Evidence is mixed regarding how familial predisposition to breast cancer affects the relation between hormone replacement therapy and risk of postmenopausal breast cancer. We investigated whether the risk difference for invasive breast cancer attributable to estrogen plus progesterone replacement therapy is greater among women with a first-degree family history of the disease. Methods This study is a longitudinal follow-up of 16,608 postmenopausal women aged 50–79 years who were enrolled between 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…Shah et al reported a 39% increase in the risk of breast cancer with postmenopausal combined estrogen and progesterone hormone therapy with OR = 1.35 (95%CI:1.16‐1.57) and OR = 1.63 (95%CI:1.22‐2.18) for less than and more than 5 years of use, respectively . However, HRT use in women with a positive family history of breast cancer was not associated with a greater incidence of breast cancer . The noninteracting effect of family history and HRT on the incidence of breast cancer was similarly demonstrated in this study also.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Shah et al reported a 39% increase in the risk of breast cancer with postmenopausal combined estrogen and progesterone hormone therapy with OR = 1.35 (95%CI:1.16‐1.57) and OR = 1.63 (95%CI:1.22‐2.18) for less than and more than 5 years of use, respectively . However, HRT use in women with a positive family history of breast cancer was not associated with a greater incidence of breast cancer . The noninteracting effect of family history and HRT on the incidence of breast cancer was similarly demonstrated in this study also.…”
Section: Discussionsupporting
confidence: 92%
“…13 However, HRT use in women with a positive family history of breast cancer was not associated with a greater incidence of breast cancer. 14 two or more was marginally significant (P = .057) and protective (B = −0.540) of a positive family history of breast cancer (adjusted OR = 0.583, 95%CI:0.334, 1.016).…”
Section: Discussionmentioning
confidence: 97%
“…In the WHI estrogen plus progestin trial, breast cancer incidence did not significantly differ on the basis of age, BMI, Gail risk score (18,20), or first-degree family history (26), but increased with previous use of oral contraceptives (20) or menopausal therapy with estrogen plus progestin (18,20) and with current smoking (20). Age also had no effect on the relationship between hormone therapy and breast cancer incidence in the WHI estrogen-only trial (2), but risks were significantly reduced in women without a previous biopsy indicating benign breast disease or a family history of breast cancer (63).…”
Section: Variability Of Outcomes In Population Subgroupsmentioning
confidence: 99%
“…Since the 1960s, Taiwan has become increasingly industrialized . The Westernization of the citizens’ lifestyle has been suggested as a plausible cause of the rapid increase in FIBC incidence rates in Taiwan .…”
Section: Discussionmentioning
confidence: 99%